Seating arrangement in learning English: teachers’ perception - Adolo, Fitria Magfira; Akhmad, Enni; Jannatussholihah, Siti (English Education Department, 2022)
Learning enviroment affects students' learning qualitiyin the class. It needs teachers' ability to manage the seating arrangement. This study aimed to describe the English teachers' perception on the seating arrangement and to find out obstacles faced by teachers when applying seating arrangement. This study employed descriptive study with a qualitative approach. The result of the study indicated that the perception of the English teachers on the seating arrangement pattern is vey important. The class arrangement that has been applied is the seating pattern in the form of a separated table and solo work. With the aim that class conditions are fun and not monotonous. Obstacles that were often faced by the teachers; a) Student conditions, they often make noise when changed the seating arrangement pattern. Even, they were not only hard to manage but also protested to change; b) Classroom condition, a narrow room is also an inhibiting factor for the application of the seating arrangement pattern. Therefore, this research study is to encourage teachers to create the learning environment which affect to the students’ learning quality.